Pragmatism and Diversity
XI, 243 p.
Keywords: Diversity is an unavoidable aspect of twenty-first century living. The authors in this volume engage in cross-difference conversations with other thinkers from earlier periods and other philosophical traditions in order to reconstruct pragmatism and cosmopolitanism in ways that are more attuned to our lived experience of diversity.